ANALISIS RASIO PENDANAAN TERHADAP PEMENUHAN KEWAJIBAN PEMBAYARAN MANFAAT PENSIUN PADA DANA PENSIUN PERKEBUNAN PTPN - Istiqomah, Nurul; Astuti, Hesti Widi (Jurnal Manajemen Magister Darmajaya, 2018)
This study aims to find out how the condition of funding ratio owned by Plantation Pension Fund (DAPENBUN), determination of funding condition and funding adequacy are based on Decree of Minister of Finance No.510/KMK.06/ 2002. The research method used qualitative method, the type of research is descriptive and the data used in this research is the form of financial statements. The results of this study shows the ratio of funding and fulfillment of pension benefit obligation (solvency ratio) of Plantation Pension Fund (DAPENBUN) in 2011-2015, the highest funding ratio in 2011 is 87.48% and the highest solvency ratio in 2011 in 92.71%. The lowest funding ratio in 2015 is 78.48% and the lowest solvency ratio in 2015 is 84.09%. It influences a funding level of DAPENBUN decreased 100% and it is in 3rd level of funding, where DAPENBUN is in the lowest level because its actuary liability is bigger than its asset and its solvency liability is bigger than its wealth for its funding.Keywords - Funding Ratio, fulfillment of pension benefit obligation.